The past, present and future of international business & management - Devinney, Timothy M. 1956-; Pedersen, Torben; Tihanyi, Laszlo, Ph. D. (Advances in international management ;, 2010)
This volume concentrates on the substantive gaps in the IB/IM field and addresses whether these gaps are resolvable with our current theoretical and methodological toolkit. This entails three specific queries about the past and present: Have our theories advanced some combination of explanation and prediction? Have our methods proven to be effective in providing rigorous, robust and consistent evidence with respect to the explanatory and predictive validity of our theories? Have we studied the right phenomena in the right way?